Theology in the flesh – embodied sensing, consciousness and the mapping of the body - Meiring, Jacob (HTS teologiese studies, 2016)
Flowing from his model for a contemporary theological anthropology as embodied sensing, the author focuses on the corporeal-linguistic turn in the 21st century and explores how his use of bodymapping, as an applied aspect of theological anthropology within the context of narrative therapy, intersects with the work of the neuro-scientist, Antonio Damasio on consciousness, and specifically his research on how the brain constantly maps the body in the brain. The author also explores the notion of sensing in the latest book of the Irish philosopher Richard Kearney and based on this, expands his model for theological anthropology to the embodied sensing of meaning.